2017
DOI: 10.18357/jcs.v42i2.17837
|View full text |Cite
|
Sign up to set email alerts
|

The Moral Experiences of Children Living in Poverty: A Focused Ethnography

Abstract: <div class="page" title="Page 1"><div class="section"><div class="layoutArea"><div class="column"><p><span>A focused ethnography was conducted in an after-school academic support program serving vulnerable populations in Montreal, Quebec, Canada. The aim of this study was to </span><span>explore the moral experiences of children living in poverty to inform on their daily experiences and moral lives. Our results highlighted that these children, who were experienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Even in the face of significant obstacles that can entail serious reprisals, young people can lead community actions that are beneficial to them and their peers, revealing the social basis of their agency. In other Montreal‐based research, young people have demonstrated agential action as they engage in community organisation activities to learn ways to navigate oppressive experiences within their schools and families or participate in research to reveal humiliating or harmful practices in a child mental health program (Montreuil, Ménard, & Carnevale, 2018; Montreuil, Saint‐Laurent, & Carnevale, 2017; Montreuil, Thibeault, McHarg, & Carnevale, 2019). That is, young people as agents can draw on social institutions that they consider supportive (i.e.…”
Section: A New Ontology Of Young Peoplementioning
confidence: 99%
See 2 more Smart Citations
“…Even in the face of significant obstacles that can entail serious reprisals, young people can lead community actions that are beneficial to them and their peers, revealing the social basis of their agency. In other Montreal‐based research, young people have demonstrated agential action as they engage in community organisation activities to learn ways to navigate oppressive experiences within their schools and families or participate in research to reveal humiliating or harmful practices in a child mental health program (Montreuil, Ménard, & Carnevale, 2018; Montreuil, Saint‐Laurent, & Carnevale, 2017; Montreuil, Thibeault, McHarg, & Carnevale, 2019). That is, young people as agents can draw on social institutions that they consider supportive (i.e.…”
Section: A New Ontology Of Young Peoplementioning
confidence: 99%
“…This process can be used with all children, regardless of age or expressive capacities, given that agential expression is not limited solely to children's verbal articulation — referring again to a ‘thick’ conception of children's voices (Carnevale, 2020). We have published demonstrations of these approaches applied to various situations, such as those described at the beginning of this paper; for example, youth with gender identity concerns (Noiseux et al., 2019), First Nations youth with cancer (Van Praagh et al., 2018), child welfare (Montreuil et al., 2017; Van Praagh et al., 2018), Tanzanian community (Sebti et al., 2019); as well as other related scenarios (Carnevale, 2012; Carnevale & Gaudreault, 2013). Below, in the final section, we illustrate how this approach can be applied in practice in our discussion of one of the concerns identified at the beginning of this paper.…”
Section: A New Ontology Of Young Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…This view is being challenged as it reinforces children and youth as passive rather than active in their health and well-being (Marjorie Montreuil & Carnevale, 2016). Recently, the perspectives of children and youth are being recognized as valuable (M Montreuil, Thibeault, McHarg, & Carnevale, 2018;Marjorie Montreuil, Saint-Laurent, & Carnevale, 2017;Riley, 2004;Sixsmith, Gabhainn, Fleming, & O'Higgins, 2007), and new research focusing on the health and well-being of children and youth are increasingly taking a child-centered approach to help capture their perspectives (Redmond, Skattebol, & Saunders, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For children and youth, many struggle to reconcile the cultural differences and have to cope with intergenerational conflict, stigmatisation and sometimes violence 12 52–55. Some also have to adapt to a new school structure (teaching styles and expectations) and often, learning in a new language 53 55. For those living in poverty and low-resource neighbourhoods, overcrowding and exposure to gangs and crime can be stressful 55 56.…”
Section: Introductionmentioning
confidence: 99%